Reading Contemporary "Bad Girls": The Transgressions and Triumphs of Madonna's "What It Feels Like For a Girl" - Marsh, Charity (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
Through an analysis of Madonna's "What it Feels Like for a Girl," I problematize the impulse to dismiss women who transgress boundaries and challenge gender norms in spite of their complicity within systems of power and privilege.